Analysis of color shift on butterfly wings by Fourier transform of images from atomic force microscopy - Kaspar, Pavel; Sobola, Dinara; Sedlák, Petr; Holcman, Vladimír; Grmela, Lubomír (Microscopy research and technique, 2019)
Butterfly wings have complex structure lending it several interesting properties. Coloration of the wing is one of the first things to encounter and the overall visual effect is in fact influenced by several factors. Chemical pigments set the base color of the wing, topographical structures on the wing scales cause color shift by interference and their arrangement into diffraction grating causes iridescence. The thin film interference can be attributed to microscopic ridges covering wing scales. Observation and calculation of the color shift on wings of Euploea mulciber species using Fourier transform of images obtained by atomic force microscopy is the focus of this article.
Keywords: mikroskopie atomárních sil; křídla zvířecí; Animals; Pigmentation; motýli; Butterflies; Fourier Analysis; zvířata; Microscopy, Atomic Force; Fourierova analýza; pigmentace; Wings, Animal